Концесія на доопрацювання підготовлених запасів шахтного поля з подальшою ліквідацією вугледобувних підприємств - Сердюк, О.С. (Економіка промисловості, 2016)
Визначено ефективну форму інвестування розвитку вугледобувних підприємств, досліджено елементи шахтного ресурсу, що можуть становити цінність для інвестора, наведено модель розрахунку економічної ефективності проектів концесії, визначено ступінь впливу інвестиційних факторів на грошовий потік беззбитковості проекту. Определена эффективная форма инвестирования развития угледобывающих предприятий, исследованы элементы шахтного ресурса, которые могут представлять ценность для инвестора, приведена модель расчета экономической эффективности проектов концессии, определена степень влияния инвестиционных факторов на денежный поток безубыточности проекта. The effects of the introduction of new pricing policies in the market of domestic coal are predicted. The optimum form of involvement of private capital to the development of state coal enterprises is identified. The feasibility of using concessions as a form of private investment in the coal industry is proved. Concession is viewed as a complex event that involves mining of coal and liquidation of the enterprise. The concept is proposed which involves the removal of mine resource in the process of liquidation in order to profit from its sale. The difference between the nominal value and practical value of mine resource is showed. The elements of the mine resource that can have high practical value are defined. Potential markets for mine resource are identified. High practical value of arch support is proved. The mine resources that could have market demand for recycled materials are determined.The peculiarities of monoprojects that are the parts of the overall concession project are given. The conditional term of realization of monoprojects is determined. The expediency of NPV method application in the context of estimation of economic efficiency of concession projects is proved. The role of cash flow breakeven in estimation of economic efficiency of concession projects is identified. The approach to the regulation of cash flow breakeven is proposed. The expediency of assessing the significance of investment factors by level of their impact on the cash flow is proved. The usage of statistical method "planning experiment" to determine the degree of influence factors on cash flow is proposed. The limit values factors used within the method of "planning experiment" are shown. The matrix of 32 experiments is formed and the regression equation that describes the degree of influence of factors on investment cash flow breakeven is calculated. "Pareto map" that reflects the importance of factors relative to cash flow breakeven is given.